Penerapan Critical Path Method (CPM) Guna Meningkatkan Efisiensi Pada Perawatan C-Check Pesawat Boeing 737-500 (PK-NAS) (Studi Kasus di PT. Merpati Maintenance Facility) - Nurdin, Riani; Arrasyid, Calvin Ali; Mauidzoh, Uyuunul (Universitas Katolik Parahyangan, 2025)
Turn Around Time (TAT) in C-Check maintenance activities is a problem that often occurs in aircraft maintenance service organizations because it requires large operational costs for technicians, and there are losses due to waiting time for aircraft operations during maintenance. This research compares company TAT with TAT using the Critical Path Method (CPM) and the percentage of man-hours efficiency from calculating the CPM method. The research object and data were collected at the PT Merpati Maintenance Facility. The types and sources of data used in research are primary and secondary. The data analysis techniques used are Turn Around Time (TAT) planning calculations and the Critical Path Method (CPM) method, as well as analyzing calculations that have been carried out using Microsoft Excel. Based on the research results, it was found that the difference in results between company planning was 18.56 or 19 work days and planning using the CPM method was 16.94 or 17 work days, so that you get more efficient time for 2 work days in carrying out C-Check maintenance with a percentage of the man hours efficiency formula of 0.087%.